Coupling spatiotemporal community assembly processes to ecosystem function - Graham,Emily; Crump,Alex R.; Resch,Charles T; Fansler,Sarah; Arntzen,Evan; Kennedy,David; Fredrickson,Jim; Stegen,James C. (PeerJ Preprints, 2016)
Community assembly processes govern shifts in species abundances in response to environmental change, yet our understanding of assembly remains largely decoupled from ecosystem function. Here, we test hypotheses regarding assembly and function across space and time using hyporheic microbial communities as a model system. We pair sampling of two habitat types (e.g., attached and unattached) through seasonal and sub-hourly hydrologic fluctuation with null modeling and temporally-explicit multivariate statistics. We demonstrate that dual selective pressures assimilate to generate compositional changes at distinct timescales among habitat types, resulting in contrasting associations of Betaproteobacteria and Thaumarchaeota with selection and with seasonal changes in aerobic metabolism. Our results culminate in a conceptual model in which selection from contrasting environments regulates taxon abundance and ecosystem function through time, with increases in function when oscillating selection opposes stable selective pressures. Our model is applicable within both macrobial and microbial ecology and presents an avenue for assimilating community assembly processes into predictions of ecosystem function.
Keywords: selection; niche; aerobic respiration; dispersal; riverbed; heterotrophy; hyporheic; microbial community structure; ammonia oxidation; Hanford